"I am a Multinational Soul on a Multicultural Globe". Multi-Cultural Identity (Re) Construction among International Degree Student Sojourners through Socialization in Intercultural Settings - Orlovskaja, Veslava (My University, 2009)
Globalization has speeded up the process of migration considerably in recent decades. Internationalization of universities has caused a rush of international students into foreign universities, and the spread of English globally has made international gatherings and communication between cultures possible. As this happens, the inevitable is at hand—multicultural identity negotiation occurs within the context of intercultural communication. The aim of this research is to show how multicultural identity is renegotiated among international student sojourners in intercultural settings. Multicultural identity means accumulation of different cultural elements, along with reshaping of national identity. This can only be accomplished through socialization in intercultural settings as well as through previous travel experience. These factors contribute to the formation of a multicultural identity or of a multicultural person in international student sojourners. Semi-structured interviews were conducted with 13 international students to find out how their cultural identity was changed through contact with other cultures‘ representatives. Five interviews are presented as cases and analyzed along with the metaphors of identity. The results showed that international student sojourners became ―multiculturalized‖ in an intercultural context.
Keywords: Sudent sojourner; multicultural identity; globalization; internationalization of universities; intercultural communication; fi=Englannin kieli|en=English language|; fi=Master's Degree Programme in Intercultural Studies in Communication and Administration|